2017
DOI: 10.1093/arclin/acx004
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Functioning in Coronary Artery Disease Patients: Associations with Thyroid Hormones, N-Terminal Pro-B-Type Natriuretic Peptide and High-Sensitivity C-Reactive Protein

Abstract: Lower fT3 concentrations and higher levels of NT-proBNP were associated with worse cognitive functioning in CAD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
1
8
2
Order By: Relevance
“…16 In addition, during rehabilitation of stable CAD patients after ACS, lower fT3 concentrations were associated with worse cognitive outcomes. 15 In contrast, in the present study, we found no association between thyroid hormones and HRQoL. However, previous studies either used different HRQoL measures, such as SF-36, or were analysing non-CAD subjects.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…16 In addition, during rehabilitation of stable CAD patients after ACS, lower fT3 concentrations were associated with worse cognitive outcomes. 15 In contrast, in the present study, we found no association between thyroid hormones and HRQoL. However, previous studies either used different HRQoL measures, such as SF-36, or were analysing non-CAD subjects.…”
Section: Discussioncontrasting
confidence: 99%
“…For example, lower thyroid hormone concentrations were associated with greater and more severe neuropsychiatric symptoms, worse HRQoL and greater fatigue symptom severity in patients after acute myocardial infarction. [13][14][15] Decreased serum free triiodothyronine (fT3) and thyroid stimulating hormone (TSH) concentrations were associated with worse HRQoL of primary brain tumour patients. 16 N-terminal pro-B-type natriuretic peptide (NT-pro-BNP) is a well-established marker of heart failure and a predictor of impaired cardiovascular prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…27 There are also several human studies showing a relation between thyroid function and cognitive function in coronary artery disease patients and especially in patients with Hashimoto. 10,28 But a recent trial that examined thyroid hormone replacement therapy for subclinical hypothyroidism in individuals ≥65 years did not find beneficial effects across patient-reported outcomes, including executive cognitive function. 29 However, it might be questioned whether at this age, cognitive dysfunction is predominantly related to early dementia symptoms, commonly caused by cerebral-vascular problems or (early stages of) Alzheimer disease.…”
Section: Discussionmentioning
confidence: 99%
“…NT-proBNP is produced by cardiac myocytes in response to volume overload and is used for diagnosis and monitoring of heart failure patients [25]. Greater serum NT-proBNP concentrations were previously implicated in worse general cognitive functioning and increased risk of cognitive impairment [26,27], decreased perception speed [28], and executive function [29] in community-dwelling adults and in cardiac patients. It was recently shown in BT patients that elevated NT-proBNP levels are associated with a greater five years mortality risk and greater global cognitive decline [25].…”
Section: Introductionmentioning
confidence: 99%